The Adenosine Receptors (The Receptors,, 2018)
This book traces the history of adenosine receptor research from molecular biology to medicinal chemistry to behavior, including their implications in disease and potential strategies as therapeutic targets. It provides the reader with a comprehensive overview of the adenosine receptors that includes information on all subtypes - A1, A2A, A2B and A3. Aspects addressed include the most up to date information on their functional distribution in the nervous and peripheral systems, behavioral roles in inflammation, cancer, pain and neurological diseases such as Huntington's disease, Epilepsy, Parkinson's disease and Alzheimer's disease.